PENGARUH E-LKPD IPAS BERBASIS PROBLEM-BASED LEARNING TERHADAP LITERASI BENCANA PADA SISWA KELAS V DI SD RAWAN BENCANA KOTA BENGKULU - Fadhilah, Laili; Noperman, Feri; Yusnia, Yusnia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of Problem-Based Learning (PBL)-based IPAS E-Worksheets (E-LKPD) on disaster literacy among fifth-grade students in disaster-prone elementary schools in Bengkulu City. This research employed a quantitative approach using a quasi-experimental design with a Matching Only Pretest-Posttest Control Group. The experimental class (n=30) received instruction using PBL-based IPAS E-LKPD, while the control class (n=30) received conventional instruction. Data were collected using pretest and posttest instruments comprising multiple-choice questions and attitude questionnaires as well as observation sheets. The results revealed differences in posttest mean scores: knowledge (80.57 > 65.00), attitude (83.60 > 78.73), and skills (85.10 > 81.63). All hypothesis tests produced significance values below 0.05. Therefore, the use of PBL-based IPAS E-LKPD has a significant effect on disaster literacy among fifth-grade students in disaster-prone elementary schools in Bengkulu City.